2014
DOI: 10.1007/s13762-014-0568-1
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of arsenic in rice through deficit irrigation in field and use of filtered water in kitchen

Abstract: An experiment was conducted in an arsenicaffected area of West Bengal, India, with the aim of alleviating arsenic toxicity from food chain through water management in rice field and modification of cooking procedure of the same grain in kitchen. Three regimes of deficit irrigation, viz. intermittent ponding, saturation and aerobic condition were tested in field against continuous ponding, i.e. local farmers' practice. Produced grains were cooked in traditional method with both arsenic-contaminated and filtered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A recent study found that oxic and anoxic conditions play an important role for As uptake in rice grains (Wu et al 2017 ). It should be borne in mind, however, that our calculations were based on rice samples directly collected from the field and that the As concentration in the steamed or cooked grain needs to be further investigated for health risk assessment purposes; a recent study has found that the procedure of rice cooking could also influence the As content in rice (Basu et al 2015 ). Another study on Bangladeshi inhabitants showed a significant positive correlation between cooked rice intake and urinary total As content (Melkonian et al 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study found that oxic and anoxic conditions play an important role for As uptake in rice grains (Wu et al 2017 ). It should be borne in mind, however, that our calculations were based on rice samples directly collected from the field and that the As concentration in the steamed or cooked grain needs to be further investigated for health risk assessment purposes; a recent study has found that the procedure of rice cooking could also influence the As content in rice (Basu et al 2015 ). Another study on Bangladeshi inhabitants showed a significant positive correlation between cooked rice intake and urinary total As content (Melkonian et al 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the primary areas for mitigation surrounds the use of deficit irrigation schemes such as aerobic cultivation and intermittent ponding, which have been shown to reduce the concentrations of arsenic in the rice without significantly reducing the yield (Senanayake and Mukherji 2014;Basu et al 2015;Mukherjee et al 2017). These schemes promote water efficiency as irrigation is limited and puts the crops under a certain degree of water stress.…”
Section: Infrastructurementioning
confidence: 99%
“…Simple changes in the processing of food can help to reduce the arsenic intake and a key enabler of this mitigation strategy is the availability and use of safe drinking water (Carbonell-Barrachina et al 2009). Using high volumes of arsenic-free water to cook contaminated rice and vegetables reduces the concentration of arsenic in the diet, as opposed to using arsenic-affected water that compounds the exposure (Carbonell- Barrachina et al 2009;Sharma et al 2014;Basu et al 2015). This is heavily dependent on the perception of the hazard and the motivation of households to use safe drinking-water sources wherever possible, despite potential inconveniences.…”
Section: Behaviormentioning
confidence: 99%